Diversity and systematics of thrips species on legumes / Assoc. Prof. Dr. Fauziah Ismail and Prof. Dr. Wan Mohamad Wan Abd. Kadir - Ismail, Fauziah; Wan Abd. Kadir, Wan Mohamad (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2004)
Thrips is now becoming one of the important insect pests on vegetable crops particularly in the family of Leguminoceae. The most common legumes attacked by thrips are long beans and French beans. Thrips are small and minute insects and belong to the order Thysanoptera. It is too small and easily unnoticed with naked eyes, yet collectively spectacular when they are in a vast number. They are widespread throughout the world with a preponderance of tropical species, many temperate ones and even a few species extending to arctic regions. Many thrips are destructive pests to plants, especially grain crops, fruits, vegetables and ornamentals. The feeding activities of thrips result in plant deformities, scarring, and loss of yield and in some cases, transmission of plant pathogens. Thrips mostly attack flowers, buds, young shoots or leaves of plants. The attacks on the leaves cause discolouration and the leaves develop a distorted aspect between the lateral veins, whereas the attack on flowers also cause them to be discoloured and dried. Both leaf surfaces are covered with small droplets of a reddish fluid, voided by thrips that gradually changes to blackish in colour. Severely damaged leaves turn to yellow and drop to the ground. Four selected states which have been chosen, namely, Johor, Melaka, Negeri Sembilan and Selangor. A total of three thrips species were found namely Megalurothrips usitatus, Thrips palmi and Thrips taiwanus. In Johor, two species of thrips were found namely Megalurothrips usitatus and Thrips taiwanus. In Melaka, three species were identified namely Megalurothrips usitatus, Thrips palmi and Thrips taiwanus whereas in Negeri Sembilan and Selangor only one species was identified namely Megalurothrips usitatus. From the monitoring and collection of thrips in Johor, Melaka, Negeri Sembilan and Selangor, Megalurothrips usitatus was the most abundant on long beans.